Efficient and economical three-component synthesis of pyrano[2,3-d]thiazol derivatives using deep eutectic solvent - Fatemeh Mohammad; Najmedin Azizi; Zohreh Mirjafari; Javad Mokhtari (Journal of Ionic Liquids)
Deep eutectic solvents (DESs), a promising class of ionic liquids, have emerged as versatile and sustainable media for organic synthesis due to their unique physicochemical properties. In this study, we report an efficient and practical one-pot, three-component protocol for the synthesis of substituted pyrano[2,3-d]thiazoles using aromatic aldehydes, malononitrile, and thiazolidinediones in DES. The methodology offers several advantages, including operational simplicity, broad substrate scope, shorter reaction times, and good to excellent yields. Importantly, the DES serves both as a solvent and a catalyst, providing a cost-effective and environmentally friendly alternative to conventional methods. Furthermore, the DES system demonstrates excellent recyclability, maintaining its catalytic performance and product yields over seven consecutive cycles. This approach highlights the potential of DESs as green media for the development of sustainable synthetic transformations.